Implications of Digital Transformation of Land Registration Processes as Seen in The Face of Agrarian Law - Lia Gulianti; Nia Kurniati; Elis Nurhayati (JURNAL AKTA, 2025)
Digital transformation in the Land Registration Process is part of the modernization of land administration and services in Indonesia. The digitalization of the land registration process is regulated by Regulation of the Minister of ATR/BPN No. 3 of 2023 concerning the Issuance of Electronic Documents. The land registration activity refers to Government Regulation No. 24 of 1997 and Government Regulation No. 18 of 2021. The legal umbrella for the digitalization of land registration is regulated in the UUITE, UUSPK, PP PSTP, PBBSSN, and Presidential Decree SPBE. Digital transformation involves electronic land registration, making the shift to the UUPA a specialist lesson from the perspective of legal certainty and legal protection. There are crucial issues regarding the electronic system, the legality and evidentiary power of electronic certificates, especially in the event of a dispute or system failure. Meanwhile, the electronic system also affects legal protection faced with data security risks, the potential for digital maladministration, resulting in losses arising from system errors. The implications of digital transformation in the land registration process in the UUPA and PP are required to evaluate the extent to which the implementation of electronic systems is able to guarantee Legal Certainty which must be clear, consistent and predictable as well as Legal Protection (guarantee provided by the legal system to protect every right to land ownership for the community, as well as identifying the problem of disharmony or overlapping rules as a logical consequence of legal implications and digital implications. This qualitative research applies a juridical-normative approach and is enriched with in-depth interview data. Of course, the most fundamental implication is the emergence of disharmony of rules between lex specialis, namely the UUPA with Lex Generalis UU ITE and technical regulations that support digitalization, and overlapping regulations related to the protection of ownership rights and the validity of electronic evidence (for example between BPN government regulations and the ITE Law). This condition hinders the realization of the goals of Indonesia's Transformation Infrastructure in the land sector. This research recommends comprehensive harmonization of regulations, the establishment of clear legal responsibilities in the digitalization of the land registration process.